Ahi Evran, the Sage of Tradesmen and Craftsmen and the Ahi-Order From Past to Present - Erol Ülgen (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
“Wisdom, Morals, Science, Work”The Ahi-Order organization draws attention as a socioeconomic, political, and military power during the Seljuk and Ottoman Empire(s). The structure of this organization comprising tradesmen and craftsmen was shaped by both Turkistan and Iranian Turks. With the victory of Malazgirt, the doors of Anatolia were opened to the Turks. Then, the great Turkish migrations began from Asian lands into Anatolia. Mongolian attacks also had an effect on this migration. The Turks, who settled in villages, towns, and cities in Anatolia, established bazaars and markets with new names. In these bazaars, they provided employment and production and constituted markets to sell their produce. With the rules they set, the members of the Ahi-Order organization tried to ensure the stability of socioeconomic life. They fulfilled the food, beverage, and other needs of the people with the products they had produced in bazaars and markets. TheAhi-Order organization was founded all over Anatolia during the period of the Beyliks that were formed after the Seljuk state. This organization also played an active role in the establishment of the Ottoman Empire. The Ahi-Order organization turned into a guild beginning from the 16th century. Then, it continued its activities as a “gedik.” Later, it lost its authority over the tradesmen and the public, ending up with no effect on them at the beginning of the 20th century. In this study, the structuring of the Ahi-Order organization in Anatolia will be described. In addition, Ahi Evran, the founder of the organization and the sage of tanners, the roles of the Ahi community during the establishment of the Ottoman state, the loss of their functions afterward, and the formation of the tradesmen and craftsmen guilds in the Republican period in Turkey are expounded in this study. Last, research about the Ahi culture from the 1950s until this day will also find mention.